SOURCE LOCALIZATION AND MAPPING OF CHEMICAL GAS CONTAMINATED AREA WITH MULTI UAV - Aris Prabowo, Yaqub
In the field of CBRN (Chemical, Biological, Radiological, and Nuclear), hazardous substances can be caused by industrial accidents, acts of terrorism, or natural disasters, resulting in mass and significant damage to an area. Currently, most industries or certain strategic areas use static CBRN sensors to obtain maps of hazardous substance distribution. In reality, statically mounted sensors can be damaged due to explosions, cannot reach all areas, and are expensive because many sensors need to be installed. Therefore, an unmanned or olfactory robot is needed. An olfactory robot is a robot equipped with sensors that can detect CBRN substances. In this study, the problem is limited to map chemical substances or gases only. To map chemical gases in a wide outdoor environment, a robot with good maneuvering, scalability, and flexibility capabilities, such as a rotary-wing type Unmanned Aerial Vehicle (UAV), is required. A UAV equipped with a chemical gas sensor can be commanded to move based on chemical gas readings in contaminated areas. Multi-UAVs are used to speed up the source localization and distribution mapping mission in a large environment. A research of how to control one or several UAVs for chemical gas source localization and distribution mapping is addressed in this dissertation. It is assumed that there is a warning due to a gas leak in a certain area, either from an alarm installed or from reports from the surrounding community. After receiving the warning, the UAV will be flown to carry out reconnaissance in the area. The purpose of the reconnaissance is to locate the source of the gas and estimate the gas distribution map. The predicted location of the source of the gas is useful for the neutralization process, stopping the exposed gas leak while the estimated gas distribution map will be useful for assisting the evacuation and mitigation process. Because the flight time is limited, multi UAVs cannot explore the entire area in the environment. Therefore, each UAV must effectively carry out exploitation and exploration in the area defined as the chemical gas-exposed area. In this case, exploitation means the UAV heading towards the source of the gas, and exploration means the UAV heading towards another area that is not the source of the gas.